História da Matemática em contextos da Educação Matemática: contribuições do GPHM - Baroni, Rosa Lúcia Sverzut [UNESP]; Teixeira, Marcos Vieira [UNESP]; Nobre, Sergio Roberto [UNESP] (My University, 2011)
In this article we tried to show the paths outlined during the past years by the Research Group on History of Mathematics and/or its relations with Mathematics Education (GPHM) at UNESP in Rio Claro - Brazil, as well as the contributions we believe we have made to Mathematics Education. The group's production has focused on issues that address the history of institutions and characters, linked to the history of disciplines, concepts and learning materials. Also, in broader terms of mathematics education, this article presents results from research that supports the understanding of teachers' conceptions about the use of History of Mathematics in the classroom; material on the history of mathematics accessible to the teacher; the presence of the history of mathematics in textbooks; proposed introductions of real numbers; and the subject of Analysis in teacher education and training.
History of mathematics in mathematics education context: Contributions of GPHM
Keywords: Group on history of mathematics; History of mathematics and mathematics education; Researches in history of mathematics